The Effect of Working Capital Management on Profitability in Manufacturing Company Listed in Indonesia Stock Exchange - Yuli Anwar (STIE Binaniaga, 2018)
Profitability of manufacturing companies in Indonesia is influenced by various financial factors that can be measured using financial ratios. The purpose of this study is to analyze the effect of cash turnover, average collection period of receivables, and inventory turnover to profitability on manufacturing companies listed on the Indonesia Stock Exchange. The population of this research is manufacturing company of consumer goods industry sector listed in Indonesia Stock Exchange period 2011-2015 period. Sampling method used was purposive sampling and 23 companies were obtained as sample. The method of analysis used is multiple regression analysis. Based on the result of t test, cash turnover is positively related and significant to profitability. While the average collection period of receivables has a negative and significant impact on profitability. Inventory turnover has no significant effect on profitability. The results simultaneously with F test show that all independent variables have significant effect to ptofitability. The adjusted R square value of 0.135 indicates that 13.5% profitability can be explained by independent variables of cash turnover, average collection period and inventory turnover. While the rest of 86.5% is explained by other variables.Keywords: Return on investment, cash turnover, average collection period and inventory turnover.